Application of solid phase microextraction in gaharu essential oil analysis - Pravina, Ashok Kumar (2008)
The gaharu essential oil is important for the evaluation of the important compounds that makes it valuable and quality of the wood. Extraction of oil, sample preparation, concentration and isolation of analytes, greatly influences the reliable and accurate analysis of food. Solid phase microextraction (SPME) is a new sample preparation technique using fused silica fiber that is coated on the outside with an appropriate stationary phase. In this work, a simple, rapid and sensitive method was developed for the determination of compounds in fragrant wood Aquilaria spp. from the family of Thymelaeaceae, which was based on headspace solid phase microextraction (HS-SPME) followed by gas chromatography-mass spectrometry (GC-MS). The gaharu essential oil was extracted by hydroditillation and prepared by two different fibers, CAR/PDMS and PDMS/DVB. The extraction parameters of fiber coating were systemically analyzed. Finally, GC-MS following HS-SPME was applied to determination of compounds in gaharu essential oil with two different fibers. The experiment results suggest that the proposed method provided an alternative and novel approach to the study of components in gaharu and SPME fibers.